(untitled) (Tempo e Argumento, 2021)
The article aims to analyze the magazine Ilustração Brasileira. Between 1901 and 1902 twelve issues were published all of them printed in France. In the Brazilian historiography, one can find many mentions regarding the magazine, but they are always brief and superficial. Ilustração belongs to the set of periodicals founded in the beginning of twenty century and they were already able to print photographs, thanks to the new technological process. Despite being widely cited, there is no systematic studies about this periodical and one do not have data about its objectives and who was responsible for the project. Fragmentary and rare information collected from newspapers, associated with the analysis of content and collaborators of the monthly, provide some clues that help to clarify, at least part, of the problem and characterize the nature of the publication, founded at a time when technical innovations opened up new possibilities for illustrated magazines.